Serum lipid and protein profiles of theileria equi seropositive and seronegative horses - İbrahim Balkaya; Özgür Kaynar; Armağan Erdem Ütük; Fatma Çiğdem Pişkin (Eurasian Journal of Veterinary Sciences)
Aim: This study aims at determining serum protein and lipid profiles in Theileria equi seropositive and seronegative horses. Materials and Methods: Theileria equi seropositivity and seronegativity at horses were tested by IFAT. Having analyzed the blood sera of horses by SDS-PAGE and HPTLC, serum protein and lipid profiles were detected respectively. Differences between seropositive and seronegative horses were tried to be determined based on the results obtained by said analysis. Results: It was detected that there was a significant increase in 23, 52, 103, 176, 200 and 240 kDa protein levels of seropositive horses. Additionally, globulin levels of T. equi seropositive animals were observed to have increased, although albumin levels of both healthy and T. equi seropositive horses were similar. At serum lipid profile, seropositive horses were observed to be at overall lipolysis; among the total amount of lipid, particularly reduced hydrocarbon rates as well as increased diacylglycerol levels were detected. A slight increase in phospholipids and a slight decrease in cholesterol levels were found in seropositive horses. Conclusion: Mentioned changes at both protein and lipid profiles suggest that these horses have not fully recovered despite the fact that they survived acute infection.